PENGARUH SUDUT PUNTIR TERHADAP TEGANGAN DAN REGANGAN - Ramang Magga (Program Studi Matematika, Universitas Tadulako, 2010)
This research aims to study the effect of torsion angle on the stresses and strains on the material in this case steel and brass. Data collection was performed with the addition of a torsional angle to 1o in materials, material length between 65 mm to 85 mm. Results obtained on different materials with the same length showed that the stress on the steel material is greater than brass (424.415 kgf/mm2 vs. 190.987 kgf/mm2) and the same material (brass) with different length showed that the length of 85 mm smaller voltage longer than 65 mm (190.987 kgf/mm2 vs. 341.89 kgf/mm2).